FACTORS AFFECTING THE TIMELINESS OF DISTRIBUTION OF SCHOOL OPERATIONAL ASSISTANCE FUNDS (BOS PROGRAM) AT SMK MUHAMMADIYAH DELANGGU IN 2020/2021ACADEMIC YEAR - Slamet Prihatin; Sri Laksmi Pardanawati; Indra Lila Kusuma (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
BOS is a fund implementation of policies to expand the distribution of access to education. The purpose of this research is to determine the factors that affect the timeliness of BOS distribution at SMK Muhammadiyah Delanggu in the Academic Year 2020/2021. This research is a qualitative descriptive study. The main data used are observation and document review also additional interviews. The data was analyzed in 3 steps, data collection, data reduction and data display. The results showed that the process of implementing, taking, distributing and using BOS at SMK Muhammadiyah Delanggu was in accordance with government instructions or JUKNIS. The distribution of BOS has also been right on target in accordance with the needs of students and schools in order to improve the quality. The distribution can also be said to be on time because it is supported by the productivity of staffs who are motivated to distribute funds on time. The workloads are seemly balanced for each staff. The used of proper facilities also increase the factor of timeliness.